Great minds of the western intellectual tradition. Part 6 modernism and the age of analysis. - Staloff, Darren 1961-; Markos, Louis; Dalton, Dennis G.; Solomon, Robert C.; Risjord, Mark W. 1960-; Kellner, Douglas 1943-; Burgstaller, Andreas (The great courses., 2000)
Lectures based on the seminar course at Columbia University on Western intellectual history augmented by additional lectures by selected "guest" lecturers. Gives a guided tour through 3,000 years of Western thought.